Malaysian Chinese Consumer Behaviours: Heterogeneity in Ethnicity and Acculturation Influence on Consumer’s Perceived Value in Consumption - Ong, Jean Chii (2010)
The rise of China’s economy has contributed to dramatic increase of ethnic Chinese-related consumer research. However, those researches are mainly tailored to enhance knowledge of Chinese consumers in the Mainland China or Overseas Chinese in Western countries. In fact, the Malaysian Chinese is unique and highly distinctive among the ethnic Chinese. They are living in multicultural environment and having highly westernised lifestyle. Thus, this dissertation is attempt to explore new insight and develop further knowledge of Malaysian Chinese consumers’ (aged 25 – 34) behaviour which has been under-researched for sometimes.